Observation of ionospheric height changes at chumphon near the magnetic equator - Attaviriyasuwon, Rungchai; Boonchuk, Thikumporn; Leelaruji, Nipha; Hemmakom, Narong (My University, 2005)
This paper presents the ionospheric height variation for station near the magnetic equator at Chumphon campus, King Mongkut's Institute of Technology Ladkrabang which located at longitude 99.3 °E latitude 10.7 ° N. Ionogram was obtained every 15 minutes during equinox period. All data was used to determine apparent height (h'F) and critical frequency (fof2), respectively, by using data analysis of ionogram. This paper remains in predicting spread F onset base on the ionospheric height changes only. Although we have observations during a month, the height variation anomaly and we found that the spread F occurrences seem to be related to time of appearance. © 2005 IEEE.
Keywords: Apparent height; Critical frequency; Scintillation; Spread F